A modular zinc finger adaptor accelerates the covalent linkage of proteins at specific locations on DNA nanoscaffolds. Issue 6 (2nd December 2014) - Nakata, Eiji; Dinh, Huyen; Ngo, Tien Anh; Saimura, Masayuki; Morii, Takashi
Abstract : A modular adaptor assists efficient occupation of specific addresses on DNA nanostructures by proteins of interest through a covalent linkage. Abstract : A modular adaptor consisting of a sequence-specific DNA binding zinc finger protein and a self-ligating protein-tag was developed to expedite efficient formation of a covalent linkage between an individual protein molecule and the programmed address modified with a tag-substrate on the DNA nanostructure.